2016
DOI: 10.1096/fj.201500127
|View full text |Cite
|
Sign up to set email alerts
|

Importance of adipocyte cyclooxygenase‐2 and prostaglandin E 2 ‐prostaglandin E receptor 3 signaling in the development of obesity‐induced adipose tissue inflammation and insulin resistance

Abstract: ABSTRACT:We examined the involvement of adipocyte cyclooxygenase-2 (COX-2) and prostaglandin E 2 (PGE 2 )-prostaglandin E receptor (EP)3-mediated signaling during hypertrophy and hypoxia in the development of obesityassociated adipose tissue (AT) inflammation and insulin resistance. The experiments were conducted with high-fat diet (HFD)-induced obese rats, db/db mice, human subjects, and 3T3-L1 and the human Simpson-Golabi-Behmel syndrome (SGBS) adipocytes; the groups were treated with selective inhibitors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 54 publications
(80 reference statements)
4
78
0
1
Order By: Relevance
“…Our results showed that StAR overexpression increased Ser473 phosphorylation of Akt both in muscle and epididymal adipose tissue, while reduced the level of pIRS1 Ser307 in muscle of obese mice, indicating StAR could protect obese mice against the progress of type 2 diabetes, and improve the impairment of insulin signaling pathway. Recent findings have revealed a relationship between adipocyte hypertrophy and systemic low grade inflammation [Chan et al, 2016]. Recent findings have revealed a relationship between adipocyte hypertrophy and systemic low grade inflammation [Chan et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that StAR overexpression increased Ser473 phosphorylation of Akt both in muscle and epididymal adipose tissue, while reduced the level of pIRS1 Ser307 in muscle of obese mice, indicating StAR could protect obese mice against the progress of type 2 diabetes, and improve the impairment of insulin signaling pathway. Recent findings have revealed a relationship between adipocyte hypertrophy and systemic low grade inflammation [Chan et al, 2016]. Recent findings have revealed a relationship between adipocyte hypertrophy and systemic low grade inflammation [Chan et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins (PGs) are powerful lipid mediators that influence the homeostasis of several organs and tissues. PGE 2 plays a major role in inducing macrophage recruitment during adipocyte lipolysis (Chan, Hsiao, Chang, Wabitsch, & Hsieh, ). In the present study, the addition of 10 n m TCDD enhanced PGE 2 production (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our recent study [63] has further demonstrated that COX-2 mediated PGE 2 EP3 signaling during the development of adipocyte hypertrophy and hypoxia is important to recruit and interact with adipose immune cells to amplify the inflammatory responses in adipose tissue, which is also causally linked to the development of systemic insulin resistance.…”
Section: Othersmentioning
confidence: 94%